Research in economic history. Vol. 29 - Hanes, Christopher; Wolcott, Susan (Emerald, 2013)
Research in Economic History is a well-established and well-cited journal which has presented work by leading researchers in the field of economic history, including economists, historians and demographers.
Keywords: Social Science -- Anthropology -- General.; Economic history.; Economics.; elektronické knihy; electronic books